Fluorescence lifetime-based contrast enhancement of indocyanine green-labeled tumors - Kumar, Anand T. N; Carp, Stefan A; Yang, Jing; Ross, Alana; Medarova, Zdravka; Ran, Chongzhao (Journal of biomedical optics, 2017)
Although the development of tumor-targeted fluorescent probes is a major area of investigation, it will be several years before these probes are realized for clinical use. Here, we report an approach that employs indocyanine-green (ICG), a clinically approved, nontargeted dye, in conjunction with fluorescence lifetime (FLT) detection to provide high accuracy for tumor-tissue identification in mouse models of subcutaneous human breast and brain tmors. The improved performance relies on the distinct FLTs of ICG within tumors versus tissue autofluorescence and is further aided by the well-known enhanced permeability and retention of ICG in tumors and the clearance of ICG from normal tissue several hours after intravenous injection. We demonstrate that FLT detection can provide more than 98% sensitivity and specificity, and a 10-fold reduction in error rates compared to intensity-based detection. Our studies suggest the significant potential of FLT-contrast for accurate tumor-tissue identification using ICG and other targeted probes under development, both for intraoperative imaging and for ex-vivo margin assessment of surgical specimens.